2001
DOI: 10.1073/pnas.231313098
|View full text |Cite
|
Sign up to set email alerts
|

Structure of trichodiene synthase from Fusarium sporotrichioides provides mechanistic inferences on the terpene cyclization cascade

Abstract: The x-ray crystal structure of recombinant trichodiene synthase from Fusarium sporotrichioides has been determined to 2.5-Å resolution, both unliganded and complexed with inorganic pyrophosphate. This reaction product coordinates to three Mg 2؉ ions near the mouth of the active site cleft. A comparison of the liganded and unliganded structures reveals a ligand-induced conformational change that closes the mouth of the active site cleft. Binding of the substrate farnesyl diphosphate similarly may trigger this c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
306
0
13

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 253 publications
(333 citation statements)
references
References 39 publications
7
306
0
13
Order By: Relevance
“…Small alterations in the structure of this region may have a significant impact in the product specificity of the terpene synthases. In sesquiterpene synthases, a kink also appears to be present in helix G of tobacco TEAS (Starks et al, 1997) ( Figure 5B; PDB: 5EAS) and the corresponding helices of Streptomyces pentalenene synthase (Lesburg et al, 1997) (PDB: 1PS1), Fusarium sporotrichoides trichodiene synthase (Rynkiewicz et al, 2001) (PDB: 1JFA), and Penicillium roqueforti aristolochene synthase (Caruthers et al, 2000) (PDB: 1DI1), further supporting the conservation of this deformation and its potential functional importance in both mono-and sesquiterpene synthases.…”
Section: Deciphering the Molecular Determinants Of Product Specificitymentioning
confidence: 68%
See 2 more Smart Citations
“…Small alterations in the structure of this region may have a significant impact in the product specificity of the terpene synthases. In sesquiterpene synthases, a kink also appears to be present in helix G of tobacco TEAS (Starks et al, 1997) ( Figure 5B; PDB: 5EAS) and the corresponding helices of Streptomyces pentalenene synthase (Lesburg et al, 1997) (PDB: 1PS1), Fusarium sporotrichoides trichodiene synthase (Rynkiewicz et al, 2001) (PDB: 1JFA), and Penicillium roqueforti aristolochene synthase (Caruthers et al, 2000) (PDB: 1DI1), further supporting the conservation of this deformation and its potential functional importance in both mono-and sesquiterpene synthases.…”
Section: Deciphering the Molecular Determinants Of Product Specificitymentioning
confidence: 68%
“…Disruption of the hydrogen bonding network by the presence of a Pro at position 450 contributes to the formation of a kink between helices a18 and a19 and the exposure of the carbonyl oxygens of Ile-446 and Gly-447 to the active-site cavity. It has been proposed that an important aspect of the catalytic mechanism of terpene synthases may be the stabilization of the unstable carbocationic intermediates by local partial charges in the catalytic pocket (Lesburg et al, 1997;Starks et al, 1997;Rynkiewicz et al, 2001). It is therefore possible that the observed deformation of helix a18 is an essential structural feature of these enzymes.…”
Section: Deciphering the Molecular Determinants Of Product Specificitymentioning
confidence: 99%
See 1 more Smart Citation
“…2). It has been established from mechanistic studies and crystal structures of several class I enzymes that the associated DDXXD motif is involved in binding divalent metal ions, generally Mg 21 (Lesburg et al, 1997;Starks et al, 1997;Rynkiewicz et al, 2001). These divalent metal ions are involved in both binding the pyrophosphate group and catalyzing ionization and, therefore, are required for class I pyrophosphate ionization-initiated catalysis (Christianson, 2006).…”
mentioning
confidence: 99%
“…78 Although the two proteins have little sequence similarity and cyclize FPP to entirely different sesquiterpenes, they share an all α-helical fold and a highly conserved pair of Mg 2+ -binding domains that have a vital role in binding and activation of the allylic diphosphate substrate. These first structures were followed shortly thereafter by those of trichodiene synthase 79 and aristolochene synthase (Figure 11b), 80,81 In collaboration with Rod Croteau, David's laboratory also solved the crystal structure of the monoterpene synthase, bornyl diphosphate synthase. 82 These studies confirmed the universal all-helical fold of the sesquiterpene and monoterpene synthases, and have provided detailed pictures of the organization of the active sites of these remarkable, synthetically versatile cyclases.…”
Section: Enzymology and Molecular Genetics Of Natural Product Biosyntmentioning
confidence: 99%